Evaluation of Alternative Rations for Feeding Guinea Pigs in the Growth-fattening Stages - L Gaibor; J Usca; H Herrera; I Salgado (ESPOCH Congresses, 2023)
Abstract The objective of the research was to evaluate the use of alternative rations for feeding guinea pigs in the growth-fattening stages. The experimental units were made up of a total of 80 guinea pigs, 40 males and 40 females. A completely random design was applied in a combinatorial arrangement of factors, where factor A: alternative rations had 4 levels and factor B: sex had 2 levels (males and females), and carrying out the evaluation of different variables such as initial weight, final weight, weight gain, total feed intake, feed conversion, carcass weight, carcass yield, all this in addition to the mortality variable, these measurements had an evaluation period of 75 days, the same as the investigation lasted. For the statistical analysis, the experimental results were subjected to an analysis of Variance (ADEVA) and separation of means according to Tukey's methodology at a significance level (P ≤ 0.05), resulting in significant differences in the feed conversion variable. While for the rest of the variables we found highly significant differences. It was concluded that the best treatment is that of the male guinea pigs that were fed with T2 since they contribute to improving the feed conversion rates without affecting the productive behavior of the livestock. As per the results obtained from this investigation, it is recommended to disseminate to small and medium producers of guinea pigs.